Infectious Salmon Anemia Virus Specifically Binds to and Hydrolyzes 4-O-Acetylated Sialic Acids - Hellebø, Audny (American Society for Microbiology, 2004)
Infectious salmon anemia virus (ISAV) is the causative agent of infections in farmed Atlantic salmon. ISAV presumably represents a new genus within the Orthomyxoviridae. ISAV has been shown earlier to exhibit a receptor-destroying activity, which was defined as an acetylesterase with unknown specificity. We have analyzed the substrate specificity of the ISAV esterase in detail. Purified ISAV hydrolyzed free 5-N-acetyl-4-O-acetyl neuraminic acid. In addition, the purified 9-O-acetylated sialic acid derivative was also hydrolyzed, but at lower rates. When we used a glycosidically bound substrate, ISAV was unable to hydrolyze 9-O-acetylated sialic acid, which represents the major substrate for the influenza C virus esterase. ISAV completely de-O-acetylated glycoprotein-bound 5-N-acetyl-4-O-acetyl neuraminic acid. Thus, the enzymatic activity of the hemagglutinin-esterase of ISAV is comparable to that of the sialate-4-O-esterases of murine coronaviruses and related group 2 coronaviruses. In addition, we found that ISAV specifically binds to glycoproteins containing 4-O-acetylated sialic acids. Both the ISAV esterase and recombinant rat coronavirus esterase specific for 4-O-acetylated sialic acids hydrolyzed ISAV receptors on horse and rabbit erythrocytes, indicating that this sialic acid represents a receptor determinant for ISAV.